Quantifying decentralization: a blockchain-based finance / Indra Putra Badlishah - Badlishah, Indra Putra (Faculty of Business Management, 2018)
Ever since the creation of Blockchain, its disruptive decentralized nature has been said to be both beneficial and harmful to the current financial system. The need for innovation even in the financial sectors have been demandingly increasing, as costefficient alternatives are being preferred above all else. Past researchers have claimed that the Blockchain's adaptive system to be beneficial to the system, claiming it to provide cost reductions, transparency, auditability, management efficiency and many more. Although various claims by past researchers indicated the former, there are, however, none who, in their earnest effort, have presented their findings in a more quantitative form. This study therefore intends to quantify the value of decentralization of the Blockchain technology, by studying the relationship between the investment on Blockchain venture capitals and Bitcoin, for the purpose of providing a basis for recommendation to the implementation of this technology in other financial areas. This statistical study is conducted based on the data collected from the daily records of Bitcoin's respective information, which are annualized to a period of 6 years starting from 2012. Several tests such as the linear regression model will be conducted to measure the relationship between each variable. This study expects to find a significant relationship between all the variables, hence implying that the Blockchain framework to be partially beneficial if adopted to our current financial system.